Perturbation of a nonautonomous problem in ℝn - Capelato, Erika [UNESP]; Schiabel-Silva, K.; Silva, R. P. [UNESP] (Wiley, 2013)
In this paper, we prove a stability result about the asymptotic dynamics of a perturbed nonautonomous evolution equation in ℝn governed by a maximal monotone operator. Copyright © 2013 John Wiley & Sons, Ltd. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: nonautonomous systems; p-laplacian; pullback attractors; upper semicontinuity of attractors; Asymptotic dynamics; Evolution equations; Maximal monotone operators; Non-autonomous system; Nonautonomous; P-Laplacian; Pullback attractors; Upper semi-continuity; Engineering; Mathematical techniques; Dynamical systems